The Effect of Aerobic Exercise Accompanied by Music on Pain, Quality of Life, and Well-Being in Patients with Fibromyalgia Syndrome - Tan, Asiye; Dinçer, Berna (İstanbul Üniversitesi, 2024)
Fibromyalgia is a medical issue characterised by increased sensitivity to all stimuli. This sensitivity often manifests as joint stiffness, chronic pain at multiple tender points, and systemic symptoms such as cognitive dysfunction, sleep disorders, anxiety, fatigue, and depressive episodes. Fibromyalgia occurs without any identifiable underlying organic disease. Listening to music while exercising has been found to have many advantages in various of physical activities. It may enhance good emotions, enhance physical performance, decrease the perception of effort, and improve physiological efficiency. Furthermore, music has beneficial impact on patients neurological and endocrine systems, evoking significant emotional and cognitive reactions. It also regulates the mental and physiological functions of humans and provides a balance between oxygen and blood in the brain, and wordless music is effective for training pain. In this article, the effects of physical activity accompanied by music on the body in patients with fibromyalgia syndrome, the results of studies on music and exercise, and possible results obtained when music and exercise are used together are discussed. Bacause of the literature review, physical activity with music was found to have a positive effect on reducing fibromyalgia symptoms.
Keywords: Fibromyalgia; Physical exercise; Music; Pain; Quality of life; Psychological well-being